Twelve angry librarians - James, Miranda (James, Miranda. Cat in the stacks mystery., 2017)
"The New York Times bestselling author of No Cats Allowed and Arsenic and Old Books is back with more Southern charm and beguiling mystery as Charlie and Diesel must find a killer in a room full of librarians... Light-hearted librarian Charlie Harris is known around his hometown of Athena, Mississippi, for walking his cat, a rescued Maine Coon named Diesel. But he may soon be taken for a walk himself--in handcuffs... Charlie is stressed out. The Southern Academic Libraries Association is holding this year's annual meeting at Athena College. Since Charlie is the interim library director, he must deliver the welcome speech to all the visiting librarians. And as if that weren't bad enough, the keynote address will be delivered by Charlie's old nemesis from library school. It's been thirty years since Charlie has seen Gavin Fong, and he's still an insufferable know-it-all capable of getting under everyone's skin. In his keynote, Gavin puts forth a most unpopular opinion: that degreed librarians will be obsolete in the academic libraries of the future. So, when Gavin drops dead, no one seems too upset... But Charlie, who was seen having a heated argument with Gavin the day before, has jumped to the top of the suspect list. Now Charlie and Diesel must check out every clue to refine their search for the real killer among them before the next book Charlie reads comes from a prison library.."--